Studies on the gasification of coconut shells with air and steam - Dimagiba, Ely P.
Experimental studies on the gasification of coconut shells with the use of a hand-operated gas producer revealed that coconut shells is highly suitable for gas producer operation. It did not possess caking characteristics so that proper distribution of the gases, which is an essential factor for successful gasification, occurred in the fuel bed. The tar evolved which deposited on the surfaces of the gas passages could be removed without difficulty. With respect to calorific value, the gas produced from coconut shells was found to contain 130.39 to 142.48 Btu/cu. ft. at favorable operating conditions as compared with the calorific value of coke producer gas which is 126.1 Btu/cu. ft. when using hand-operated producer as given in Technical Data on Fuel by Spiers (1952).